DNA Book - Kawai, Jun; Hayashizaki, Yoshihide (Genome Research, 2003)
We propose herein a new method of DNA distribution, whereby DNA clones or PCR products are printed directly onto the pages of books and delivered to users along with relevant scientific information. DNA sheets, comprising water-soluble paper onto which DNA is spotted, can be bound into books. Readers can easily extract the DNA fragments from DNA sheets and amplify them using PCR. We show that DNA sheets can withstand various conditions that may be experienced during bookbinding and delivery, such as high temperatures and humidity. Almost all genes (95%–100% of randomly selected RIKEN mouse cDNA clones) were recovered successfully by use of PCR. Readers can start their experiments after a 2-h PCR amplification without waiting for the delivery of DNA clones. The DNA Book thus provides a novel method for delivering DNA in a timely and cost-effective manner. A sample DNA sheet (carrying RIKEN mouse cDNA clones encoding genes of enzymes for the TCA cycle) is included in this issue for field-testing. We would greatly appreciate it if readers could attempt to extract DNA and report the results and whether the DNA sheet was shipped to readers in good condition.
10.1101/gr.914203